Coming home - Ruth, Greg 1970- (Feiwel and Friends, 2014)
Follows the emotions of a young boy as he waits at an airport for a family member to return home from serving in the military
Keywords: Children of military personnel / Fiction; Families of military personnel / Fiction; Soldiers / Fiction; Children of military personnel / Juvenile fiction; Mothers and sons / Juvenile fiction; Homecoming / Juvenile fiction; Picture books for children; Children of military personnel; Homecoming; Mothers and sons